Invisible belongings: Carolinian practices of personhood and space as moral principles - Susanne Kuehling (Pacific Geographies, 2022)
Based on field research and published sources, this paper examines Micronesian migration in regards to principles of order and values on their home atolls. For Carolinians, place names and personal names are part of the web of intangible knowledge that can serve to assure certain positions and rights. They unfold the untold facts of gender and hierarchy and can be used as a peephole into social practice. Names and places represent stability and continuity in an otherwise fluid world. Migrants, I argue, can use such shared experiences of their “invisible belongings” to re-create some sense of home and build a community based on versions of these principles and values.